Economic Analysis of Cashew Apple Value Chain within the Collines Department of Benin - AKANRO, Raoul; ATANASSO, Marie Odile; DOSSOU, JOSEPH (My University, 2022)
This study aims at providing an economic analysis of the valorisation of cashew apples as a means of significantly improving the income of the actors of this value chain in Benin. The sample of our study covers 110 participants and 30 groups in the cashew apple value chain within the Collines department during the 2020-2021 season. In terms of methodological approach, indicators of financial profitability of processing units were estimated. The results of this study reveal that on average, the income derived from cashew apples harvesting contributed to a 6% reduction in poverty of the harvesters. Poverty levels of the cashew apple juice traders reduced by 3.36% as a result of the income generated from the sale of the produce. Finally, processors of the cashew apples have sufficient income to take them out from below the poverty line with 135.8% reduction in poverty. Furthermore, we noted that 71% of the apple juice produced in the Collines department is exported to WAEMU countries, France, Germany and Israel.
Keywords: Value Chain; Poverty Line; Profitability Indicators; Cashew